Evaluation of lightning location using measured induced voltage obtained from distribution power networks - Izadi M.; Kadir M.Z.A.A.; Osman M.; Hajikhani M. (Taylor and Francis Ltd., 2023)
Electric lines; Electric power transmission networks; Electromagnetic fields; Location; Renewable energy resources; Risk assessment; Distribution power networks; Electromagnetic field components; Ground flash densities; Lightning current waves; Lightning induced voltage; Lightning risk assessment; Renewable energy generation; Renewable energy source; Lightning